2015
DOI: 10.18869/acadpub.cmm.1.4.1
|View full text |Cite
|
Sign up to set email alerts
|

A survey of the etiological agents of scalp and nail dermatophytosis in Yazd, Iran in 2014-2015

Abstract: Background and Purpose:Tinea capitis and tinea unguium are regarded as global public health concerns. The purpose of the present study was to identify the etiological agents of tinea capitis and tinea unguium in patients, referring to the Central Laboratory of Yazd University of Medical Sciences, Yazd, Iran.Materials and Methods:This study was conducted during 2014-2015. Skin scraping, scalp hair, and nail clipping specimens were collected from 134 patients (80 males and 54 females) with clinical features sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 15 publications
0
9
1
Order By: Relevance
“…In addition, the maceration of periungual tissue caused by the use of manicure tools can result cross-infection among people who use this service. 27,28 However, this finding is in contrast to other studies who reported tinea corporis, 21 tinea capitis 29 and tinea cruris 30 as the commonest clinical manifestations than tinea unguium. Tinea capitis is the second most common form of tinea and accounted 24.1% of all dermatomycosis.…”
Section: Discussioncontrasting
confidence: 89%
See 4 more Smart Citations
“…In addition, the maceration of periungual tissue caused by the use of manicure tools can result cross-infection among people who use this service. 27,28 However, this finding is in contrast to other studies who reported tinea corporis, 21 tinea capitis 29 and tinea cruris 30 as the commonest clinical manifestations than tinea unguium. Tinea capitis is the second most common form of tinea and accounted 24.1% of all dermatomycosis.…”
Section: Discussioncontrasting
confidence: 89%
“…This is similar to previous studies. 27 , 28 Several authors suggest that inability to maintain good nail care and cosmetic reasons, reduced growth rate of the ungual plate, frequent housework, poor peripheral circulation and an increase in trauma rates could play an important role in this manifestation. 25 , 28 The high prevalence of dermatomycosis on toenails and the importance of this site concerning dermatomycosis are reported in several studies.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations